NUTRIENTS QUANTITIES EXTRACTED BY BERMUDA GRASS IN FUNCTION OF NITROGEN DOSES - Lima, Claudinei Paulo de; Backes, Clarice; Marques Santos, Alessandro Jose; Fernandes, Dirceu Maximino [UNESP]; Villas Boas, Roberto Lyra [UNESP]; Oliveira, Mauricio Roberto de [UNESP] (Univ Federal Uberlandia, 2015)
Nitrogen provides the greatest answers in grass growth. The objective of this work was to evaluate the total extraction of nutrients by the bermudagrass due to nitrogen levels. The experiment was conduced in a grass property, located in Capela do Alto - SP. The experimental design was a randomized blocks, with five treatments and four replications. The treatments consisted of five N doses: 0, 150, 300, 450 and 600 kg ha(-1). After each grass cut were collected clippings and determined dry matter and macronutrients content. After sod harvest, it was determined the dry matter extracted with the withdrawal of it and the nutrients concentration. The amounts of macronutrients were calculated by the product of dry weight by their concentration. With the withdrawal of clippings cut during the cycle there was a great extraction of nutrients, 204; 18; 101; 22; 10 and 27 kg ha(-1) for N, P, K, Ca, Mg e S, respectively. The amount of nutrients needed to promote 100% of grass soil coverage are 219.5, 27, 174.1, 31.8, 13.4 and 39.9 kg ha(-1), of N, P, K, Ca, Mg and S, respectively.
Keywords: Cynodon dactylon; Fertilization; Clippings; Extraction